PELATIHAN PENGOLAHAN PRODUK TURUNAN DARI JAHE DAN PINANG DI RUMAH PRODUKSI MINERBAL (MINUMAN HERBAL) KENALI ASAM BAWAH, KOTA BARU, JAMBI - Uce Lestari; Martha Veronica; Dilla Fitri Salsabila; Safrida Safrida (Universitas Jambi, 2023)
ABSTRACTThe Minerbal (Herbal Drinks) Production House located in Kenali Asam Bawah sub-district, Kota Baru Jambi is one of the business groups supported by Pertamina Hulu Rokan Zone 1 Field Jambi. This Minerbal (Herbal Drinks) production house business group has produced many herbal drinks based on ginger and areca nuts such as instant ginger granules, instant areca nut granules and traditional herbal medicine but has not yet developed a variety of other product innovations, especially functional food products. The problem encountered in this Mineralbal production house is that there is limited knowledge regarding techniques for processing ginger and areca nut into other ginger and areca nut derivative products such as functional food or health snacks. Based on the above, the products from the Minerbal production house business were developed into functional food products or health snacks such as areca ginger jelly candy, areca nut candy and areca nut ginger marshmallows as an endurance enhancer. This Community Service (PKM) aims to strengthen business capacity and develop the Minerbal production house business into effective innovations such as jelly candy and marshmallows and can open up employment opportunities in empowering and improving the economy of the Lower Recognition Asam community. The methods in this PKM include counseling regarding the benefits and nutritional content of ginger and areca nuts as well as demonstrations on making jelly candies and marshmallows based on ginger and areca nuts. The PKM results obtained areca ginger jelly candy and areca ginger marshmallows which will be used as superior products for the Minerbal production house in Kenali Asam Bawah sub-district. From the results of monitoring and evaluation of PKM activities, it was found that the Minerbal Production House had produced jelly candy and areca ginger marshmallows and had been introduced to the PKK women's bazaar in Jambi City.Key words: areca ginger, jelly candy, marshmallow, food ABSTRAKRumah Produksi Minerbal (Minuman Herbal) yang berada di kelurahan Kenali Asam Bawah Kota Baru Jambi merupakan salah satu kelompok usaha binaan dari Pertamina Hulu Rokan Zona 1 Field Jambi. Kelompok usaha rumah produksi Minerbal (Minuman Herbal) ini telah banyak memproduksi minuman herbal berbasis jahe dan pinang seperti granul instan jahe, granul instan pinang dan jamu tradisional tetapi belum ada pengembangan variasi inovasi produk lain terutama produk pangan fungsional. Adapun permasalahan yang ditemui pada rumah produksi Minerbal ini adalah adanya keterbatasan pengetahuan mengenai teknik pengolahan jahe dan pinang menjadi produk turunan jahe dan pinang lain seperti pangan fungsional atau cemilan Kesehatan. Berdasarkan hal diatas maka produk hasil usaha rumah produksi Minerbal dikembangkan menjadi produk pangan fungsional atau cemilan kesehatan seperti permen jelly jahe pinang, permen pinang dan marshmallow jahe pinang sebagai peningkat daya tahan. Pengabdian Kepada Masyarakat (PKM) ini bertujuan untuk penguatan kapasitas usaha dan pengembangan usaha rumah produksi Minerbal menjadi inovasi tepat guna seperti permen jelly dan marshmallow serta dapat membuka usaha lapangan pekerjaan dalam pemberdayaan dan peningkatan perekonomian masyarakat Kenali Asam Bawah. Metode dalam PKM ini meliputi penyuluhan terkait manfaat dan kandungan gizi dari jahe dan pinang serta demonstrasi pembuatan permen jelly dan marshmallow berbasis jahe dan pinang. Hasil PKM diperoleh permen jelly jahe pinang dan marshmallow jahe pinang yang akan dijadikan produk unggulan rumah produksi Minerbal kelurahan Kenali Asam Bawah. Dari hasil monitoring evaluasi kegiatan PKM ini ditemukan bahwa Rumah Produksi Minerbal telah memproduksi permen jelly dan marshmallow jahe pinang dan telah diperkenalkan pada bazar ibu-ibu PKK kota Jambi.Kata kunci: jahe pinang, permen jelly, marshmallow, pangan